X + 7y = 0, 2x-8y = 22 & le;

X + 7y = 0, 2x-8y = 22 & le;
Anonim

Antworten:

# (x, y) bis (7, -1) #

Erläuterung:

# x + 7y = 0to (1) #

# 2x-8y = 22to (2) #

# "aus Gleichung" (1) tox = -7yto (3) #

# "ersetzen" x = -7y "in Gleichung" (2) #

# 2 (-7y) -8y = 22 #

# -22y = 22 #

# "beide Seiten durch" -22 # teilen

# y = 22 / (- 22) = - 1 #

# "ersetze" y = -1 "in Gleichung" (3) #

# x = -7 (-1) = 7 #

# "Schnittpunkt" = (7, -1) #

Graph {(y + 1 / 7x) (y-1 / 4x + 11/4) ((x-7) ^ 2 + (y + 1) ^ 2-0.04) = 0 -10, 10, -5, 5}